Sociology 201/ - Ericksen, Eugene (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course has four objectives, to provide you with understandings of (1) basic methods of descriptive statistics, like means, medians, quartile spreads, standard deviations, and skewness, (2) random variation and how different samples selected from the same population may provide different results, (3) the basic idea of statistical inference, i.e., how we make judgments about what is the population that provided the sample result that we have observed, and (4) how to evaluate possible associations between two variables.